EVALUATION OF OPHTHALMIC DRUG REFILL PROJECT IN A HOSPITAL - Aumsurbcher, Rapee; Lochidamnuay, Surasit (Thai Bulletin of Pharmaceutical Sciences, 2025)
This study evaluated the ophthalmic drug refill project at a hospital for patients with universal health coverage by using the CIPP Model (Context, Input, Process, Product Model) to collect data from 11 hospital officers and 64 patient participants by purposive sampling. Data was collected through interviews with hospital officers from December 2022 to June 2023 and from patient questionnaires from May 2022 to November 2022. The results were analyzed using descriptive statistics and content analysis. The results showed that the drug refill project’s objective is to reduce the hospital’s financial burden on patients’ excessive treatment costs, which are not reimbursed by referral hospitals. Also, support is lacking in regard to a project budget, hospital personnel, a patient database system, troubleshooting guidelines, and an evaluation system. Furthermore, the patient selection criteria was deemed inappropriate and patients expressed dissatisfaction over the inconvenience of traveling. Most hospital personnel agreed that the drug refill project has not been successful in resolving financial problems. Therefore, guidelines and policies for the drug refill project should be established. Furthermore, it will be necessary to develop in-patient support for an online rights verification system, a mail-order drug delivery system, follow-up services for ophthalmic diseases, remote consulting services from pharmacists at no additional cost, and a drug refill service at an accredited pharmacy.